(untitled) (Texas Journal of Medical Science, 2023)
Mesial occlusion is a frequent dental situation characterised via the higher dental arch being placed too some distance ahead in relation to the decrease dental arch. This malocclusion can lead to a variety of purposeful and aesthetic issues. Fortunately, elastics have emerged as an nice cure modality for correcting mesial occlusion. This article pursuits to discover the considerable function that elastics play in the cure of mesial occlusion